The sensitivity of diesel engine performance to fuel injection parameters at various operating points - Gambrill, Richard (2004)
This thesis describes research undertaken to establish the advantages and disadvantages of using high pressure common rail fuel injection systems with multiple injection capabilities. The areas covered are detailed as follows.